Writing and Difference / Translated, with an Introduction and Additional Notes, by Alan Bass - Derrida Jacques (Rouledge, 2008)
The book that changed the way we think. Translator's Introduction, Force and Signification, Cogito and the History of Madness, Edmond Jabes and the Question of the Book, Violence and Metaphysics: An Essay on the Thought of Emmanuel Levinas, ''Genesis and Structure'' and Phenomenology, La Parole Soufflee, Freud and the Scene of Writing, The Theater of Cruelty and the Closure of Representation, From Restricted to General Economy: A Hegelianism Without Reserve, Structure and Sign and Play in the Discourse of the Human Sciences, Ellipsis, Notes, Sources.